Pancreaticoduodenectomy for pancreatic ductal adenocarcinoma: a French multicentre prospective evaluation of resection margins in 150 evaluable specimens. Issue 1 (7th March 2013) - Delpero, Jean Robert; Bachellier, Philippe; Regenet, Nicolas; Le Treut, Yves Patrice; Paye, François; Carrere, Nicolas; Sauvanet, Alain; Autret, Aurélie; Turrini, Olivier; Monges‐Ranchin, Geneviève; Boher, Jean Marie
Abstract Objectives This study aimed to determine the impact of a standardized pathological protocol on resection margin status after pancreaticoduodenectomy (PD) for ductal adenocarcinoma. Methods A total of 150 patients operated during 2008–2010 were included in a prospective multicentre study using a 'quality protocol'. Multicolour inking by the surgeon identified three resection margins: the portal vein–superior mesenteric vein margin (PV‐SMVm) or mesenterico–portal vein groove; the superior mesenteric artery margin (SMAm), and the posterior margin. Resection margins were stratified by 0.5‐mm increments (range: 0–2.0 mm). Pancreatic neck, bile duct and intestinal margins were also analysed. Correlations between histopathological factors and survival in the 0‐mm resection margin group were analysed. Results Thirty‐six patients (24%) had a PV‐SMV resection (PV‐SMVR). An analysis of resections categorized according to margin distances of 0 mm, <1.0 mm, <1.5 mm and <2.0 mm confirmed R1 resections in 35 (23%), 91 (61%), 94 (63%) and 107 (71%) patients, respectively. The most frequently invaded resection margin was the PV‐SMVm (35% of all patients) and PV‐SMVR was the only factor correlated with a higher risk for at least one 0‐mm positive resection margin on multivariate analysis (P < 0.001). Two‐year progression‐free survival (PFS) and median PFS time in patients with R0 and R1 resections (at 0 mm), respectively, were 42.0% and 26.5%, and 19.5 months and 10.5 months, respectively (P = 0.02). A positive PV‐SMVm and SMAm had significant impact on PFS, whereas a positive posterior margin had no impact. Conclusions Pancreaticoduodenectomy requiring PV‐SMVR was associated with a higher risk for R1 resection. The standardization of histopathological analysis has a clinically relevant impact on PFS data.